Analysis of Morphological Reduplication in Luganda Lexical Categories (JULACE: Journal of the University of Namibia Language Centre, 2023)
Reduplication is a morphological process in which the root/stem of a word or part of it is repeated. Reduplication is divided into different types such as full, partial, rhyming, ablaut, reduplication in baby talk and reduplication in onomatopoeia. This study deals only with full reduplication in Luganda lexical categories. The main objective of the study is to analyse the morphological reduplication in Luganda lexical categories. Specifically, the study identifies Luganda lexical categories that undergo reduplication, analyses reduplicated patterns using Morphological Doubling Theory (MDT), and explains the semantic functions of reduplication in Luganda lexical categories. Data collection included both primary and secondary data, where primary data included interviews where three pure native speakers and four teachers who teach Luganda in Rakai district were involved. Some words used in this study collected from different documents and sources include the Luganda-English dictionary, the Holy Bible (Old and New Testament) and Luganda proverbs and songs. Lexical questionnaires developed by the researcher were used. The analyses show that Luganda lexical categories undergo full reduplication in the morphological process. The recommendation and suggestions of this study are that similar studies of full reduplication in other Bantu languages should be conducted to give an overall description pertaining to this phenomenon.
Keywords: Key Words: Lexical categories of speech, Morphological process, Full reduplication, Morphological doubling